Da Paraíba ao Estado do Maranhão: trajetórias de governo na américa portuguesa (séculos XVII e XVIII) - Santos, Fabiano Vilaça dos (Revista de História, 2009)
This article tells of the connection between the governments of Paraíba and of the State of Maranhão, in the seventeenth and eighteenth centuries, from the analysis of the careers and the movement of the agents designated to the overseas administration. The connection between the posts was supported by the criteria observed by the Portuguese crown in the selection of the colonial governors, as well as their perspectives of promotion in the royal service.